Ethnocultural Analysis of the Phenomenon of Diversity Education in the Dimension of Pluralism - Gumati, Redmon Windu (Journal of Islamicate Studies, 2020)
The Unitary State of the Republic of Indonesia has a diversity of cultures (ethnocultural), many ethnic groups, countries, religions, and different customs. This diversity sometimes and disputes in the name of religion. The spread of terrorist acts, arson, destruction of facilities and places of worship, suspicion of mutual suspicions between religious communities is evidence of the existence of these conflicts and conflicts. There have been many attempts to overcome this problem, one of which is through efforts for peace and friendship, through new strategies that are more effective and relevant. In order to gain success for the realization of the noble goal, namely peace and eternal brotherhood between people who in reality do have different religions and faiths, it is necessary to have the courage to invite them to make changes in the field of education, primarily through its diversity-based curriculum (pluralism). Through a curriculum like this, it is possible to uncover the respective religious theologies that have tended to be presented exclusively and dogmatically—a faith that usually only claims that only religion can build worldly prosperity and lead people to heaven. There are only one door and room of heaven that cannot be opened and entered except by the religion he embraces. Even though such a theology, we must admit, is very worrying and can disturb the harmony of the community of faiths. All people were required to depend on each other and share their destiny to create lasting peace.